2016
DOI: 10.4081/hpr.2016.5408
|View full text |Cite
|
Sign up to set email alerts
|

Being a victim of medical error in Brazil: an (un)real dilemma

Abstract: Medical error stems from inadequate professional conduct that is capable of producing harm to life or exacerbating the health of another, whether through act or omission. This situation has become increasingly common in Brazil and worldwide. In this study, the aim was to understand what being the victim of medical error is like and to investigate the circumstances imposed on this condition of victims in Brazil. A semi-structured interview was conducted with twelve people who had gone through situations of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A Brazilian study showed that future physicians were concerned regarding discussions on the issue given that, although they were knowledgeable on the subject, discussions and clarification on ways of working with such issue in professional life are lacking. Moreover, there seems to be a certain social pressure on future and active physicians given the difficulty experienced by the professionals involved in revealing or discussing real cases (Chehuen Neto et al, 2011;Custódio, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…A Brazilian study showed that future physicians were concerned regarding discussions on the issue given that, although they were knowledgeable on the subject, discussions and clarification on ways of working with such issue in professional life are lacking. Moreover, there seems to be a certain social pressure on future and active physicians given the difficulty experienced by the professionals involved in revealing or discussing real cases (Chehuen Neto et al, 2011;Custódio, 2016a).…”
Section: Introductionmentioning
confidence: 99%